Increased Osteoclast and Decreased Osteoblast Activity Causes Reduced Bone Mineral Density and Quality in Genetic Hypercalciuric Stone‐Forming Rats. (25th February 2020) - Krieger, Nancy S; Chen, Luojing; Becker, Jennifer; DeBoyace, Sean; Wang, Hongwei; Favus, Murray J; Bushinsky, David A
ABSTRACT: To study human idiopathic hypercalciuria (IH), we developed an animal model, genetic hypercalciuric stone‐forming (GHS) rats, whose pathophysiology parallels that in IH. All GHS rats form kidney stones and have decreased BMD and bone quality compared with the founder Sprague–Dawley (SD) rats. To understand the bone defect, we characterized osteoclast and osteoblast activity in the GHS compared with SD rats. Bone marrow cells were isolated from femurs of GHS and SD rats and cultured to optimize differentiation into osteoclasts or osteoblasts. Osteoclasts were stained for TRAcP (tartrate resistant acid phosphatase), cultured to assess resorptive activity, and analyzed for specific gene expression. Marrow stromal cells or primary neonatal calvarial cells were differentiated to osteoblasts, and osteoblastic gene expression as well as mineralization was analyzed. There was increased osteoclastogenesis and increased resorption pit formation in GHS compared with SD cultures. Osteoclasts had increased expression of cathepsin K, Tracp, and MMP9 in cells from GHS compared with SD rats. Osteoblastic gene expression and mineralization was significantly decreased. Thus, alterations in baseline activity of both osteoclasts and osteoblasts in GHS rats, led to decreased BMD and bone quality, perhaps because of their known increase in vitamin D receptors. Better understanding of the role of GHS bone cells in decreased BMD and quality may provide new strategies to mitigate the low BMD and increased fracture risk found in patients with IH. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.